Saikosaponin d Alleviates Liver Fibrosis by Negatively Regulating the ROS/NLRP3 Inflammasome Through Activating the ERβ Pathway - Zhang, Kehui; Lin, Liubing; Zhu, Yingying; Zhang, Na; Zhou, Meng’en; Li, Yong (Frontiers in Pharmacology, 2022)
Background and aims: Saikosaponin d (SSd) has a steroidal structure and significant anti-inflammatory effects. The purpose of this study was to explore the mechanism underlying SSd’s inhibitory effects on liver fibrosis. Methods: Wild-type and estrogen receptor knockout (ERKO) mice were treated with CCl4 to establish liver fibrosis mouse models. The effects of SSd on hepatic fibrogenesis were studied in these mouse models. Hepatic stellate cells (HSCs) were activated by H2O2 to investigate the potential molecular mechanisms. The establishment of the models and the degrees of inflammation and liver tissue fibrosis were evaluated by detecting changes in serum liver enzymes and liver histopathology. The expression of α-SMA and TGF-β1 was determined by immunohistochemistry. The expression and significance of NLRP3 inflammasome proteins were explored by RT-PCR and Western blotting analyses. The mitochondrial ROS-related indexes were evaluated by MitoSOX Red. Results: In wild-type and ERKO mice treated with CCl4, the fluorescence expression of mitochondrial ROS was up-regulated, while the mitochondrial membrane potential and ATP content were decreased, suggesting that the mitochondria were damaged. In addition, the expression of NLRP3 inflammatory bodies and fibrosis markers (α-SMA, TGF-β, TIMP-1, MMP-2, and Vimentin) in liver tissue increased. Furthermore, the above indexes showed the same expression trend in activated HSCs. In addition, the peripheral serum ALT and AST levels increased in CCl4-induced liver injury model mice. And HE staining showed a large number of inflammatory cell infiltration in the liver of model mice. Picric acid-Sirius staining and Masson staining showed that there was significant collagen fibrous tissue deposition in mice liver sections. IHC and WB detection confirmed that the expression of α-SMA and TGF-β1 increased. Liver fibrosis scores were also elevated. Then, after SSd intervention, the expression of ROS in wild-type mice and αERKO mice decreased, mitochondrial membrane potential recovered, ATP level increased, NLRP3 inflammasome and fibrosis indexes decreased, liver enzyme levels decreased, and liver pathology showed liver inflammation. The damage and collagen deposition were significantly relieved, the expression of α-SMA and TGF-β1 was decreased, and the fibrosis score was also decreased. More importantly, the effect of SSd in alleviating liver injury and liver fibrosis had no effect on βERKO mice. Conclusion: SSd alleviated liver fibrosis by negatively regulating the ROS/NLRP3 inflammasome through activating the ERβ pathway. By establishing liver fibrosis models using wild-type and ERKO mice, we demonstrated that SSd could alleviate liver fibrosis by inhibiting the ROS/NLRP3 inflammasome axis through activating the ERβ pathway.